Actinomyces israelli bacterial reduction using ozonated water - Torres Cueva, Andrea Nataly (2018)
Actinomyces israelii, a pathogenic microorganism of periapical tissues, is difficult to eradicate due to its need of few nutrients and oxygen to subsist, thus developing an apical periodontitis. Objective: Compare 5% ozonated water, 5.25% sodium hypochlorite and 2% chlorhexidine bactericidal effect on Actinomyces israelii Materials and methods: 40 human uniradicular root canals were inoculated with Actinomyces israelii. After irrigation with the different solutions, bacterial reduction was measured through a UFC/Plaque count. The 40 teeth were divided into 4 groups: G1: Physiological serum, G2: 5% ozonated water, G3: 2% Chlorhexidine G4: 5.25% Sodium hypochlorite. The Tukey statistical test significance level was 5%. Results: The Tukey test evidenced 0 average values for 5.25% sodium hypochlorite, 0 for 2% chlorhexidine and 0.3 for ozonated water. This test determined that 5.25% NaOCl is the first choice treatment followed by 2% chlor-hexidine, and 5% ozonated water. No significant differences were found on the ozonated water action and other solutions (<0.15). Conclusions: 5% ozonized water was effective in the bacterial reduction of A. israelli as well as 5.25% NaOCl, without significant statistical differences.